The future of unionism in the Philippine call center industry - Bool, Arlene C. (Animo Repository, 2007)
The study sought to uncover the potential of unionism in the Philippine call center industry by exploring call center employees predisposition to unionization taking into consideration their working conditions and socio-demographic factors. Employing probability proportional to size (PPS) sampling technique, the size of the sample was established using the Sloven formula at -+ 10% margin of error at 95% confidence interval or one hundred (100) respondents from the randomly chosen Metro Manila call centers Sykes Asia, Inc., Convergys Corporation and eTelecare International. Data were gathered through self-administration of survey questionnaire which captures respondents socio-demographic characteristics and conditions of employment. The data were later on analyzed using statistical tools on descriptive and causal research. Descriptive research describes the data in terms of frequency and percentage of independent variables condition of employment and socio-demographic characteristics. Causal research applied logistic regression depicting which particular independent variables predict a discrete outcome, that is, the predisposition to join trade union. The study found out that majority of the respondents - (1) were female, (2) were aged 25 years old or below with the mean age of 24.4 years, (3) finished a Bachelors Degree, (4) handled customer service and (5) had a length of service of 6 months to 1 year. It is also revealed that almost all of the respondents (1) had general knowledge, (2) believed that salary / wage rate negotiation is the most important role of trade union, (3) had an average monthly income of more than P15,000.00, and (4) experienced moderate pressure in their jobs. Nearly half of the respondents were neutral (neither happy nor unhappy) in terms of satisfaction at work. In addition, bulk of the respondents (1) worked 40 hours a week, (2) had scheduled breaks of 90 minutes per day, (3) had no problems when taking their breaks, (4) had a grave yard shift, rendering service during the interval 12 midnight to 6 oclock a.m., (5) who were on grave yard shift were female, (6) had copies of rules and regulations affecting working conditions, (7) said changes in company work rules and regulations were available, (8) said that the employers communication with the staff is designed to inform, (9) almost all of the respondents said that team meetings are part of employers communication mechanisms with staff, and (10) were predisposed to join an affordable, principled and efficient workplace union. Most importantly, the study disclosed that the following predisposition to join union is a function of the following factors or independent variables which appeared to have significant relationship: (1) average monthly income, (2) function or purpose of communication at work, (3) availability of company rules and regulations, (4) age and (5) knowledge about trade union. In essence, call center employees are predisposed to join trade union if (1) they have lower monthly income, (2) their communication mechanism at works purpose is to merely inform, (3) availability of their company rules and regulations is lesser, (4) they are younger and (5) they have greater knowledge about trade union. A closer look on the characteristics of the respondents who are predisposed in joining union exposed that majority (1) had an average monthly take home pay of P15,000 or below, (2) viewed the function or purpose of communication in their workplace was to inform, (3) said that hard copies of rules and regulations affecting working conditions were given to them or printed off for their use, (4) belonged to age bracket 25 years old and below and (5) were never trade union members but had general knowledge about trade unions.